A Study of Methyl Formate Production from Carbon Dioxide Hydrogenation in Methanol over a Copper Zinc Oxide Catalyst - Yu, K; Tsang, S (2011)
A preliminary study of the production of methyl formate (MF) from CO 2 hydrogenation in liquid methanol was carried out over a Cu/ZnO/Al2O3 based catalyst which was synthesized by a precipitation technique following a well established route. The effects of amine concentration, hydrogen pressure, temperature, CO and water addition on the activity and selectivity of MF were investigated. It is of interest to note that the addition of 1% trimethylamine can dramatically increase the initial turnover frequency with the MF being the major product. It is evident that the formation of CO2-amine adduct promotes the catalytic hydrogenation of CO2 on the surface of the catalyst. © 2010 Springer Science+Business Media, LLC.